PENGARUH KEPEMILIKAN MANEJERIAL, KEPEMILIKAN INSTITUSIONAL, DAN KEBIJAKAN HUTANG TERHADAP KEBIJAKAN DEVIDEN PADA PERUSAHAAN MANUFAKTUR DI BEI - Tongam Sartika Sitorus; Irham Fahmi (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2023)
This study aims to determine: the effect of managerial ownership on dividend policy in IDX manufacturing companies, the effect of institutional ownership on dividend policy in IDX manufacturing companies, the effect of debt policy on dividend policy in IDX manufacturing companies, and determine whether managerial ownership, institutional ownership, and policy dividends have a simultaneous effect on debt policy in IDX manufacturing companies. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2016-2020. The sampling technique is using the Purposive Sampling Method. The sample selection is carried out with the aim of being able to determine the appropriate criteria for research. The results of the study show that: There is an effect of managerial ownership on dividend policy in manufacturing companies on the IDX, with the probability value obtained on the t test of 0.0054 (5% = 0.05); there is an effect of institutional ownership on dividend policy in manufacturing companies on the IDX, with the probability value obtained on the t test of 0.0003 (5% = 0.05); there is an effect of debt policy on dividend policy in manufacturing companies on the Stock Exchange, with the acquisition of probability values on the t test of 0.0010 (5% = 0.05); and Managerial Ownership, Institutional Ownership, and Debt Policy together have a significant effect on Dividend Policy in manufacturing companies on the IDX.